Examination of the variables related to parents' irrational beliefs: a meta-analysis study - Çekiç, Ali; Korkmaz, Kübra; Cömert, Sebnem Aslan; Yildirim, Ibrahim (Frontiers in Psychology, 2025)
IntroductionThe aim of this study was to determine the variables that have been studied in relation to parents' irrational beliefs, and to examine the relationships between these variables through meta-analysis. Additionally, this study aimed to explore cultural differences in parents' irrational beliefs by conducting subgroup analyses based on the country in which the study was conducted.MethodsFifteen studies, which had been issued in the databases of Google Scholar and Web of Science (WOS) between the years of 1990 and 2023, met the inclusion criteria and were included in the analyses. In these fifteen studies, the associations of parents' irrational beliefs with twenty three different variables were examined. These variables were reorganized under the titles of “Irrational thoughts”, “Positive mental health (Parent)”, “Negative mental health (Parent)”, “Negative mental health (Child)”, “Positive behavior (Parent)”, “Negative behavior (Parent)”, “Adaptation (Parent)”, “Parent-child relationship”, “Positive characteristics (Child)” and “Irrational beliefs (Child)” in line with expert opinions. Among these variables, the effect sizes of those that included a sufficient number of studies for meta-analysis were calculated separately.Findings and conclusionAccordingly, the largest effect size was calculated between parental irrational beliefs and general irrational beliefs (0.60), and the smallest effect size was calculated between parental irrational beliefs and children's negative mental health characteristics (0.15). In the subgroup analyses conducted according to the country of the study, the largest effect sizes were observed in USA for all variables, while the lowest effect sizes were observed in Turkey.